2018
DOI: 10.1093/rheumatology/key397
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in clinical characteristics and prognosis of immunoglobulin G4–related disease: a prospective study of 403 patients

Abstract: Objectives To study the impact of sex on the clinical presentation of IgG4-related disease (IgG4-RD). Methods We prospectively enrolled 403 newly diagnosed IgG4-RD patients. We compared the demographic features, clinical manifestations, organ involvement, laboratory tests and treatment outcomes between female and male patients. The organs involved were divided into superficial organs (salivary glands, lacrimal glands, orbit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 45 publications
3
57
0
1
Order By: Relevance
“…We have known that IgG4-RD has a gender predilection [1]. Female patients present more frequently with superficial organ involvement, while male patients more frequently have internal organ involvement [20]. Similarly, our cluster analysis results indicated that cluster 2 was characterized by internal organ-dominant (male to female, 3.53:1) and cluster 3 was characterized by superficial organ-dominant (male to female, 0.94:1).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We have known that IgG4-RD has a gender predilection [1]. Female patients present more frequently with superficial organ involvement, while male patients more frequently have internal organ involvement [20]. Similarly, our cluster analysis results indicated that cluster 2 was characterized by internal organ-dominant (male to female, 3.53:1) and cluster 3 was characterized by superficial organ-dominant (male to female, 0.94:1).…”
Section: Discussionsupporting
confidence: 71%
“…The number of organs involved was determined by a review of the patient's history, physical examination, blood tests, imaging, and tissue biopsies. The organs involved were divided into superficial organs (i.e., salivary glands, lacrimal glands, orbit, sinus, and skin) and internal organs (i.e., all of the other organs) [20][21][22]. Lymph nodes were not taken into account when assessing the involvement of the superficial/internal organs [20].…”
Section: Baseline Clinical Evaluation and Laboratory Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team at Peking Union Medical College Hospital (PUMCH) established an IgG4-RD cohort in 2011. In previous studies, we prospectively described the clinical characteristics 11 , sex disparities 12 , radiographic presentation 13 and histopathologic features 14 of patients with IgG4-RD in our cohort. The present study focused on the Data collection.…”
mentioning
confidence: 99%
“…31 (3) © 2020 Esmon Publicidad doi: 10.18176/jiaci.0633 [15,16]. In general, women with IgG4-RD are younger, with a higher prevalence of allergic diseases, lower levels of blood eosinophils, lower C-reactive protein (CRP), lower serum IgG4, and better prognosis of the disease [17].…”
Section: Epidemiology Of Igg4-related Diseasementioning
confidence: 99%